Tool Wear Characteristics in Machining of Hypereutectic Al-Si Alloys by Cemented Carbide Tool - Yuya KOBARU; Ryo NAGAOKA; Kenji SHIMANA; Shinichi YOSHIMITSU; Eiji KONDO (Journal of Machine Engineering)
During of hypereutectic Al-Si alloys, tool wear increases owing to the presence of silicon particles. Therefore, polycrystalline diamond tools are typically used, but they are very expensive. The purpose of this study is to examine the tool wear characteristics during the end milling of hypereutectic Al-Si alloy (A390–T6) by using comparatively inexpensive diamond-like carbon coated cemented carbide tools. Al-Si alloy was end-milled by changing the cutting speed. Our results revealed that the width of flank wear land increased monotonously with increasing of the cutting force regardless of the cutting speed. In addition, the experimental equation of the width of flank wear land was derived as a function of cutting speed and time, and it was clarified that width of flank wear land could be approximated.